Moda Produksi Petani di Desa Lora Kecamatan Mata Oleo Kabupaten Bombana - Amjudal Amjudal; Hasniah Hasniah; Zainal Zainal (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2023)
This study aims to determine the use of farmer production tools and the form of farmer production relations in Lora Village, Mata Oleo District, Bombana Regency. The theory used refers to the theory of modes of production put forward by Karl Marx. The author uses ethnographic research methods through involved observation and in-depth interviews. As for the results of the study, it can be concluded that based on the results of research on the life of farmers in Lora Village, Mata Oleo District, Bombana Regency, it can be concluded that the farmers in Lora Village, Mata Oleo District, Bombana Regency still uphold the culture of mutual cooperation and competitiveness in helping each other. Most of the farmers in Lora Village still use traditional tools to support their activities in the rice fields, but as time goes by and technological advances are very influential, especially the tools used by farmers. The form of farmer production relations in Lora Village that is running well can be seen from the cooperation between farmers and owners of water pump machines, production owners and taxi vehicle owners. All of them collaborate and work together so that all work on rice fields can run smoothly and quickly and can produce maximum yields to be able to support food needs, especially in the Bombana Regency area.